Pengaruh Kepuasan Pelanggan Terhadap Keputusan Pembelian Produk Odeng Ngodeng Cabang Solo Baru - Riana Amalia Sacrivi; Dea Ananda; Rayhan Gunaningrat (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
The independent variable in this research is the variable that is manipulated and predicted to have an influence on the dependent variable. This is known by the tolerance value and Variance Inflantion Factor (VIF) value which are used to determine positive and negative values between independent variables. There is no or no multicollinearity found in the regression model. It is found that there is no multicollinearity in the Regression Model. This shows that there is a linear relationship and influences the dependent variable. Test the Coefficient of Determination (R2) to determine the contribution of variabilitate and independent variables.